Inequities in reporting asbestos-related lung cancer: influence of smoking stigma and physician's specialty, workload and role perception. Issue 6 (10th October 2007) - Verger, P; Arnaud, S; Ferrer, S; Iarmarcovai, G; Saliba, M-L; Viau, A; Souville, M
Abstract : Objectives: To study physician barriers to workers' compensation claims for asbestos-related cancers, focusing on smokers' stigma and physicians' speciality and role perception. Methods: Cross-sectional telephone study of 486 randomly-selected general practitioners (GPs) and pulmonologists in south-eastern France. Standardised questionnaires explored their behaviour, attitudes and practices in the field of occupational health and their responses to a case vignette of a lung cancer patient with long-term occupational asbestos exposure. Randomised subgroups of GPs and pulmonologists heard alternative versions varying only as regards the worker's smoking status. We studied factors associated with the recommendation that the case vignette patient file a compensation claim with simple and multiple logistic regressions. Results: The response rate was 64.4 among GPs and 62.5 among pulmonologists. Recommending the filing of an occupational disease claim was significantly associated in multiple logistic regressions with speciality (OR 4.46; 95 CI 2.38 to 8.37, for pulmonologists vs GPs), patient's smoking status (OR 3.15; 95 CI 2.11 to 4.70, for non-smokers vs smokers), physician's workload (OR 1.83; 95 CI 1.17 to 2.88, for ⩽25 consultations per day vs >25) and role perception (OR 2.00; 95 CI 1.22 to 3.27, for those who considered completing occupational disease medical certificates to be part of their role vs those who did not). Conclusions: The results of this French study appear applicable to various countries and contexts. To make physicians and especially GPs more aware of occupational health and smoking stigma, officials and educators must give these topics higher priority during initial training and continuing medical education. Tools and equipment that take time constraints into account should be developed and disseminated to help physicians manage occupational diseases.